2013
DOI: 10.1002/cncy.21287
|View full text |Cite
|
Sign up to set email alerts
|

uCyt+/ImmunoCyt and cytology in the detection of urothelial carcinoma

Abstract: BACKGROUND:The aim of the current study was to report the results of 7422 uCyt1/ImmunoCyt and cytology analyses that were performed over the course of 9 years at the study institution for the evaluation and follow-up of patients with urothelial carcinoma. METHODS: Between January 2002 and March 2011, 2217 patients with a mean age of 69.5 years (range, 15 years-99 years) were enrolled in the current study. All patients seen for the follow-up of bladder and/or upper tract urothelial cancer as well as those with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 11 publications
(38 reference statements)
0
29
0
3
Order By: Relevance
“…Meanwhile, ICC can have a higher sensitivity than cytology for low-grade cancers (24, 25). As a result, the more expensive ICC- and FISH-based tests are commonly used to aid in the evaluation of epithelial cells deposited on slides.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, ICC can have a higher sensitivity than cytology for low-grade cancers (24, 25). As a result, the more expensive ICC- and FISH-based tests are commonly used to aid in the evaluation of epithelial cells deposited on slides.…”
Section: Resultsmentioning
confidence: 99%
“…6 Tetu et al showed that uCyt1 in combination with urinary cytology increased the sensitivity for the detection of BC up to 100%. The test tags mucin glycoprotein and carcinoembryonic antigen, both frequently expressed in urothelial cancer cells, with green and red fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…The test tags mucin glycoprotein and carcinoembryonic antigen, both frequently expressed in urothelial cancer cells, with green and red fluorescence. 6 Tetu et al showed that uCyt1 in combination with urinary cytology increased the sensitivity for the detection of BC up to 100%. Other reports on the sensitivity of uCyt1 as a single diagnostic measure range from 53% to 100% with specificities ranging from 64 to 95%, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particolare, Messing riporta una sensibilità per il carcinoma in situ (cis) del 100%, dato poi confermato da Têtu e Mian (11,12). Il valore predittivo negativo dell'ImmunoCyt/uCyt+ da solo e in combinazione è risultato del 93-95%, nei diversi studi (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Questi risultati, ormai confermati negli anni da numerosi studi sia in Nord America che in Europa, dimostrano la sicurezza della combinazione ImmunoCyt/uCyt+ con la citologia nei protocolli di sorveglianza.…”
Section: Introduzioneunclassified